2012
DOI: 10.1103/physrevb.86.075434
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-well states with image state character for Pb overlayers on Cu(111)

Abstract: We study theoretically the quantum well states (QWSs) localized in Pb overlayers on Cu(111) surface. Particular emphasis is given to the states with energies close to the vacuum level. Inclusion of the long-range image potential tail into the model potential description of the system allows us to show the effect of hybridization between QWSs and image potential states (ISs). The particle-in-a-box energy sequence characteristic for QWSs evolves into the Rydberg series converging towards the vacuum level. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…In the following we substantiate that the interband SO coupling, which explains (i) the modification of the dispersion of the α-band and (ii) the sign reversal in the momentum splitting, is independent of the supporting substrate by studying QWS in Pb/Cu(111) 35,48,[57][58][59][60] . Figure 7(a) shows the electronic structure of 8 ML Pb The results and our analysis are displayed in Fig.…”
Section: Interband Spin-orbit Coupling In Pb Qwsmentioning
confidence: 54%
See 1 more Smart Citation
“…In the following we substantiate that the interband SO coupling, which explains (i) the modification of the dispersion of the α-band and (ii) the sign reversal in the momentum splitting, is independent of the supporting substrate by studying QWS in Pb/Cu(111) 35,48,[57][58][59][60] . Figure 7(a) shows the electronic structure of 8 ML Pb The results and our analysis are displayed in Fig.…”
Section: Interband Spin-orbit Coupling In Pb Qwsmentioning
confidence: 54%
“…In the following we substantiate that the interband SO coupling, which explains (i) the modification of the dispersion of the α-band and (ii) the sign reversal in the momentum splitting, is independent of the supporting substrate by studying QWS in Pb/Cu(111) [35,48,[59][60][61][62]. structure of Pb/Bi/Si the effective mass of the α-band is significantly reduced from m = 3.2m e to 0.86m e , and the pronounced change in the dispersion is situated above the Fermi level.…”
Section: Pb/cu(111)mentioning
confidence: 55%
“…The negative value of a is a consequence of the two-dimensional character of graphene in contrast to a surface terminating a bulk metal with three-dimensional periodicity, where 0 a 0.5. However, a < 0 has been observed in case of metallic quantum-well structures [27,28] and predicted for freestanding graphene [5,13].…”
Section: Resultsmentioning
confidence: 94%
“…It was demonstrated that many properties of thin films may depend of their thickness due to modulation of the density of states at the Fermi level. This effect was mainly investigated in films consisting of simple metals [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%